From misconceptions to reasonable osteoarthritis patients therapy - O. A. Shavlovskaya; О. А. Gromova; I. Yu. Torshin; I. D. Romanov (Фармакоэкономика)
Osteoarthritis (OA) is a painful and disabling disease that affects millions of people around the world. OA is the most common form of arthritis and is characterized by joint pain and stiffness, leading to a decrease in functional activity and loss of quality of life. Approaches to OA therapy are constantly being revised, as new molecules appear, data on drugs/molecules already in use, including data on adverse events, new randomized controlled trials results, new methods of adjunctive therapy become available. OA therapy and prevention, drugs with chondroprotective properties are prescribed according to the opinion of European experts (2019): chondroitin sulfate (CS), glucosamine sulfate (GS), diacerein, avocado soybean unsaponifiables, hyaluronic acid (HA) for intra-articular administering. Only CS and GS have proven effectiveness and the level of recommendations A1, they are included in clinical recommendations and standards of the Ministry of Health of the Russian Federation (MHRF), and international recommendations according to which CS and GS should be used for a long time (up to 6 months). The article focuses on the analysis of erroneous statements regarding the classification, composition and mechanisms of action of different drugs of this group. Differences in terminology of drug groups are given, such as: chondroprotectors, symptomatic slow acting drugs for osteoarthritis (SYSADOAs), disease-modifying osteoarthritis drugs, between which an equal sign cannot be placed. Based on the analysis, a conclusion was made about erroneous attitudes towards some SYSADOAs: 1) according to the Anatomical Therapeutic Chemical Classification, the active substances CS, GS, diacerein and HA are classified as nonsteroidal anti-inflammatory drugs due to their antiinflammatory activity; 2) quite often, drugs based on bioactive concentrate of small sea fish and glycoaminoglycan-peptide complex do not belong to SYSADOAs according to any of the existing generally recognized classifications, they do not contain a sufficient amount of active substances (CS or peptides), there is no proper level of evidence, they are not included in the recommendations of international medical communities and MHRF clinical recommendations and standards. In Russia, physicians must follow MHRF clinical guidelines and standards for OA therapy.